Implementation of the HiBalance training program for Parkinson's disease in clinical settings: A feasibility study. Issue 8 (21st June 2018) - Joseph, Conran; Leavy, Breiffni; Mattsson, Sara; Falk, Lynn; Franzén, Erika
Abstract: Background: Translating evidence into practice requires adaptation to facilitate the implementation of efficacious interventions. A novel highly challenging balance training program (HiBalance) was found to improve gait, balance, and physical activity in persons with Parkinson's disease (PD) in an earlier randomized controlled trial. This study aimed to describe the adaptation process and feasibility of implementing the HiBalance program for PD within primary healthcare settings. Method: Feasibility was assessed in terms of study processes and scientific evaluation. Nine persons with mild–moderate PD were enrolled in this pre–post feasibility study. The dose of the original program was adapted by reducing therapist‐led training sessions from three to two times weekly. Outcome measures were substituted with ones more clinically feasible. One group ( n = 5) received HiBalance training three times weekly for 10 weeks while another ( n = 4) trained twice weekly plus a once weekly home exercise program (HEP). Balance performance was the primary outcome, while secondary outcomes (e.g., gait speed, physical activity level, concerns of falling, and health‐related quality of life) were also evaluated. Results: Regarding process feasibility, attendance was high (approximately 90%) in both groups, and experiences of the group and home training were positive. Newly selected outcome measures were feasible. The scientific evaluation revealed few adverse events and no serious injuries occurred. Concerning outcomes per group, the average change in balance performance and gait speed was equal to, or exceeded, the minimally worthwhile treatment effect commonly used in PD. Conclusion: The findings support the feasibility, in terms of process and scientific evaluation, of the adapted HiBalance program for implementation within clinical settings. A sufficiently powered study is required to ascertain whether the newly proposed program offers similar short and long‐term effects as the original program. Abstract : This study aimed to describe the adaptation process and feasibility of implementing the HiBalance program for PD within primary healthcare settings. Dosage changes were required, as well as more clinically suitable measures were warranted for successful translation. Regardless of these program changes, the findings support the feasibility of the adapted HiBalance program for implementation within clinical settings.